2SPD-029 Stability of nivolumab solutions after transport through pneumatic tube systems. (23rd March 2022) - Selmin, F; Camuffo, L; Vasile, F; Mangoni, G; Piccoli, M; Rivano, M; Cancanelli, L; Minghetti, P
Abstract : Background and importance: The assessment of 'in-use' stability of biotechnological medicinal products is not typically required prior to regulatory approval. However, 'in-use' conditions (ie, handling, storage, transport) could compromise product stability and, consequently, affect safety and/or efficacy. Aim and objectives: This work aimed to investigate the stability of diluted nivolumab solution after delivery in pneumatic tube systems (PTS) and the effects of residual air inside the bag. Material and methods: Due to the complexity of nivolumab, the major stability-indicating methods – turbidimetry, size exclusion chromatography-high-performance liquid chromatography (SEC-HPLC), dynamic light scattering (DLS), pH, osmolality, nanoparticle tracking analysis (NTA), nuclear magnetic resonance (NMR) – were applied based on the results of a previous forced degradation study. All experiments were also carried out after 7 days of storage at 2–8°C to investigate if the mechanical stress caused by PTS could induce instability over time. Results: All samples remained clear for the duration of the study with no precipitates or particulate matter detected with the naked eye. No change in colour or turbidity was observed over the study period. The pH of nivolumab solutions ranged from 5.8 to 6.0 over time, which was within the manufacturer's recommended pH range of approximately 6.0. Also, osmolarity did not undergo any variation, ranging from 283 to 297 mOsm/kg during the storage of all samples. All SEC-HPLC chromatograms of nivolumab were characterised by a single major peak with an elution time of 11 min and a minor signal with a retention time of around 13 min. After transportation, samples with and without air presented an identical elution profile, suggesting the absence of soluble aggregates. The percentage of high molecular weight aggregates (HMWP) remained constant in samples with and without air after 7 days. These results were confirmed by DLS and NTA. Conclusion and relevance: In this study, no differences in the main physical and chemical properties were observed in compounded nivolumab solutions after a single pass in PTS for at least 7 days of storage. The presence of an air–liquid interface inside the bag was not risk-determining for protein stability. In conclusion, these results support the possible use of PTS to deliver bags to clinical services. References and/or acknowledgements: Conflict of interest: No conflict of interest